Adaptation and psychometric properties of a brief version of the general self-efficacy scale for use with artificial intelligence (GSE-6AI) among university students - Morales-García, Wilter C.; Sairitupa-Sanchez, Liset Z.; Morales-García, Sandra B.; Morales-García, Mardel (Frontiers in Education, 2024)
Background: Individual beliefs about one's ability to carry out tasks and face challenges play a pivotal role in academic and professional formation. In the contemporary technological landscape, Artificial Intelligence (AI) is effecting profound changes across multiple sectors. Adaptation to this technology varies greatly among individuals. The integration of AI in the educational setting has necessitated a tool that measures self-efficacy concerning the adoption and use of this technology. Objective: To adapt and validate a short version of the General Self-Efficacy Scale (GSE-6) for selfefficacy in the use of Artificial Intelligence (GSE-6AI) in a university student population. Methods: An instrumental study was conducted with the participation of 469 medical students aged between 18 and 29 (M=19.71; SD=2.47). The GSE-6 was adapted to the AI context, following strict translation and cultural adaptation procedures. Its factorial structure was evaluated through confirmatory factorial analysis (CFA). Additionally, the factorial invariance of the scale based on gender was studied. Results: The GSE-6AI exhibited a unidimensional structure with excellent fit indices. All item factorial loads surpassed the recommended threshold, and both Cronbach's Alpha (α) and McDonald's Omega (ω) achieved a value of 0.91. Regarding factorial invariance by gender, the scale proved to maintain its structure and meaning in both men and women. Conclusions: The adapted GSE-6AI version is a valid and reliable tool for measuring self-efficacy in the use of Artificial Intelligence among university students. Its unidimensional structure and gender-related factorial invariance make it a robust and versatile tool for future research and practical applications in educational and technological contexts.